Evaluation of traumatic brain injury by optical technique. Issue 1 (December 2015) - Lin, Bor-Shyh; Wang, Che-Chuan; Chang, Ming-Hsien; Chio, Chung-Ching
Abstract Background Traumatic brain injury (TBI), usually due to brain shaking or impact, affects the normal brain function and may lead to severe disability or even death. However, there is paucity of information regarding changes in the physiologic state of humans or animals after brain shaking. Methods In this study, near-infrared spectroscopy (NIRS) was used to continuously monitor the concentration change of oxy-hemoglobin (HbO2) and deoxy-hemoglobin (HbR) to understand changes in the physiological state during and after brain shaking. Laser Doppler flowmetry was also used to monitor changes in cerebral blood flow under TBI to supplement the investigation. Triphenyltetrazolium chloride (TTC) staining was used to monitor changes of infarction volume corresponding to different impact strengths. Result The experimental results indicated that concentration changes of HbO2 and total-hemoglobin (HbT) were significantly related to the impact strength. The infarction volume was also significantly related to the impact strength. Conclusion Therefore, the non-invasive monitoring of concentration changes inHbO 2, HbR, andHbT using NIRS may have a clinical application for the evaluation of TBI.